Postoperative Infection in Cementless and Cemented Total Knee Arthroplasty: A Propensity Score Matched Analysis - Anis, Hiba K.; Ramanathan, Deepak; Sodhi, Nipun; Klika, Alison K.; Piuzzi, Nicolas S.; Mont, Michael A.; Higuera, Carlos A.; Molloy, Robert M. (The Journal of Knee Surgery, 2019)
The ongoing debate on fixation in total knee arthroplasty (TKA) has become increasingly relevant with its increased use in a younger patient population and the advent of novel cementless prostheses. Recent literature suggests modern cementless implants are comparable to their cemented counterparts in terms of survivorship and functional outcomes. What has not been well-assessed is whether the two modalities differ with respect to infection rates which was the purpose of this study. Specifically, a propensity score matched study population was used to compare: (1) overall infection; (2) prosthetic joint infection (PJI); and (3) surgical site infection (SSI) rates between cementless and cemented TKAs. Using a large institutional database, 3,180 consecutive primary TKAs were identified. Cementless and cemented TKA patients were propensity score matched by age (p = 0.069), sex (p = 0.395), body mass index (BMI; p = 0.308), and Charlson's comorbidity index (CCI) score (p = 0.616) in a 1:1 ratio. Univariate analysis was performed to compare 2-year overall infection rates. Infections were further analyzed separately as PJIs (deep joint infections requiring surgery) and SSIs (skin/superficial wound infections). Multivariate logistic regression was performed to evaluate infection incidences after adjusting for procedure-related factors (i.e., operative time, hospital volume, and surgeon volume). There were no significant differences between the matched cohorts in terms of overall infection rates (3.8 vs. 2.3%, p = 0.722), as well as when PJI (p = 1.000) and SSI (p = 1.000) rates were analyzed separately. Multivariate analysis revealed no significant differences in overall postoperative infection rates (p = 0.285), PJI rates (p = 0.446), or SSI rates (p = 0.453) even after adjusting for procedure-related factors. There is increasing literature investigating various outcomes demonstrating the comparable efficacies of cementless versus cemented TKAs. To the best of the author's knowledge, this was the first matched case-control study to directly compare their post-operative infection rates. The findings from this study show that post-operative infection rates were similar between fixation modalities even after accounting for a range of patient- and procedure-related factors.
Keywords: cementless; total knee arthroplasty; infection